2009
DOI: 10.1158/1078-0432.ccr-07-5023
|View full text |Cite
|
Sign up to set email alerts
|

The Double-Edged Sword of Autophagy Modulation in Cancer

Abstract: Macroautophagy (autophagy) is a lysosomal degradation pathway for the breakdown of intracellular proteins and organelles. Although constitutive autophagy is a homeostatic mechanism for intracellular recycling and metabolic regulation, autophagy is also stress responsive, in which it is important for the removal of damaged proteins and organelles. Autophagy thereby confers stress tolerance, limits damage, and sustains viability under adverse conditions. Autophagy is a tumor-suppression mechanism, yet it enables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
917
1
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,013 publications
(945 citation statements)
references
References 88 publications
17
917
1
10
Order By: Relevance
“…[56][57][58][59][60][61][62] The downstream inhibitors of autophagy chloroquine and hydroxychloroquine suppress tumor growth in a laboratory mouse model 63 and have been used in clinical trials of human patients. 56,[59][60][61][62]64 In a clinical trial, the addition of chloroquine has significantly improved median survival of patients with glioblastoma receiving conventional chemotherapy and radiotherapy. 65 However, other studies suggest that chloroquine or hydroxychloroquine is not effective in some types of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[56][57][58][59][60][61][62] The downstream inhibitors of autophagy chloroquine and hydroxychloroquine suppress tumor growth in a laboratory mouse model 63 and have been used in clinical trials of human patients. 56,[59][60][61][62]64 In a clinical trial, the addition of chloroquine has significantly improved median survival of patients with glioblastoma receiving conventional chemotherapy and radiotherapy. 65 However, other studies suggest that chloroquine or hydroxychloroquine is not effective in some types of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…ACTB was used as a loading control. many anticancer agents can induce autophagy, 17,56,62 it is critical to understand the effects of autophagy on cell survival and death when combining anticancer agents with an autophagy inhibitor. It has been demonstrated that an autophagy inhibitor can sensitize cancer cells to the treatment with some anticancer agents such as histone deacetylase (HDAC) inhibitors by taking advantage of the cell survival role of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy, or programmed cell survival, shares several common stimuli and signaling pathways with those of apoptosis (Maiuri et al, 2007). Autophagy is a tumorsuppression mechanism, yet it enables tumor-cell survival in settings of enhanced stress (Kondo et al, 2005;Mathew et al, 2007;White and DiPaola, 2009). Moreover, autophagy can degrade active caspase-8 within tumor cells (Hou et al, 2010).…”
mentioning
confidence: 99%
“…There is mounting evidence to link autophagy and cancer, 51,52 and the role of autophagy in cancer progression is still unclear. Several reports demonstrated that activation of autophagy may suppress tumor development and lead to cell death.…”
Section: Therapeutic Potential Of Mirnas and Autophagic Pathwaymentioning
confidence: 99%
“…[59][60][61] Contrary to this, other studies have shown an anticancer role by enhancing autophagy. 47,52,62,63 Table 1 provides a list of miRNAs reported with therapeutic potential for treating cancer. It seems clear that the unique oncogenes/pathways involved in autophagy, the specific tumor type and tumor environment and the disease context are some of the key factors to be considered for developing autophagy-mediated anticancer strategies.…”
Section: Therapeutic Potential Of Mirnas and Autophagic Pathwaymentioning
confidence: 99%